Optimum Sowing Date of Winter Wheat in Next 40 Years Based on DSSAT-CERES-Wheat Model - HU Yanan (Editorial Office of Smart Agriculture, 2021)
Climate change requires crop adaptation. Plantint at the suitable date is a key management technology to promote crop yield and address the impact of climate change. Wheat is one of the most important staple crops in China. Huang-Huai-Hai and Jiang-Huai regions are high-quality and high-quantity planting areas for wheat. To deal with the adverse effects of climate change and promote the winter wheat yield in Huang-Huai-Hai and Jiang-Huai regions, the optimum sowing date was identified by creating a wheat simulation with DSSAT CERES-Wheat model. The simulation experiment was designed with 51 management inputs of sowing date and 4 climate scenarios (RCPs) under baseline period (1985－2004) and 40 years in future for three representative stations in the study region. The optimum sowing data of winter wheat was corresponding to the simulation set with highest yield in each site. The characters of changes in climate factors during the growth period and the optimum sowing date among the different period were detected, and the yield increase planted at the optimum sowing date was quantified. The results showed that, in the future, the climate during winter wheat growth period showed a trend of warming and drying would shorten the growth period. The optimum sowing date would be postponed with the rise of temperature, and the decrease of latitude in all periods and under various climate scenarios. Relative to the baseline period, the maximum delay days of the optimal sowing date increased from north to south during 2030s, which were 5 days, 8 days and 13 days at the three representative stations, respectively. The optimum sowing times in 2050s were delayed in different degrees compared with that in 2030s. The largest postponed days at each station was at the RCP8.5 scenario in 2050s. Adopting the management of optimum planting date could mitigate climatic negative effects and was in varying degrees of yield increasing effect at three sites. The smallest increase occurred in Huang-Huai-Hai north region, while Huang-Huai-Hai south region and Jiang-Huai region had the relatively higher yield increasement about 2%－4%. Therefore, the present study demonstrated an effective management of optimum sowing date to promote winter wheat yield under climate change in Huang-Huai-Hai and Jiang-Huai regions.